Topical issues of the modern applied ethics - Shramko Ярослав (Actual Problems of Mind, 2023)
This article provides an overview of contemporary studies in the field of applied ethics carried out within the framework of analytical moral philosophy. The systematic application of the tools of normative ethics to the consideration of practical issues of human and social life forms the field of applied (or practical) ethics, which analyses the moral aspects of vital problems that are at the very heart of public debate and usually have great social significance, in particular, for making important decisions by both state structures and specific agents of society, whether it be social groups or individuals. Among the branches of modern applied ethics, business ethics, environmental ethics and biomedical ethics are usually distinguished as the most relevant and dynamically developing. In addition, applied ethics actively discusses a set of problems that affect key issues of life and death, such as the death penalty, euthanasia, suicide, relations between the sexes, attitudes towards various minorities and many others. The article concludes that the development of applied ethics within the framework of analytical and philosophical research, on the one hand, contributes to the revealing and comprehensive processing of various empirical material that is effectively used to confirm classical normative theories, and on the other hand, provides a significant impetus for further development of the newest concepts in the field of normative ethics.